Can We Commit Future Managers to Honesty? - Jacquemet, Nicolas; Luchini, Stéphane; Rosaz, Julie; Shogren, Jason F. (Frontiers in Psychology, 2021)
In a competitive business environment, dishonesty can pay. Self-interested executives and managers can have incentive to shade the truth for personal gain. In response, the business community has considered how to commit these executives and managers to a higher ethical standard. The MBA Oath and the Dutch Bankers Oath are examples of such a commitment device. The question we test herein is whether the oath can be used as an effective form of ethics management for future executives/managers --- who for our experiment we recruited from a leading French business school --- by actually improving their honesty. Using a classic Sender-Receiver strategic game experiment, we reinforce professional identity by pre-selecting the group to which Receivers belong. This allows us to determine whether taking the oath deters lying among future managers. Our results suggest ``yes and no.'' We observe that these future executives/managers who took a solemn honesty oath as a Sender were (a) significantly more likely to tell the truth when the lie was detrimental to the Receiver, but (b) were not more likely to tell the truth when the lie was mutually beneficial to both the Sender and Receiver. A joint product of our design is our ability to measure in-group bias in lying behavior in our population of subjects (comparing behavior of subjects in the same and different business schools). The experiment provides clear evidence of a lack of such bias.